Torque teno viruses exhaust and imprint the human immune system via the HLA-E/NKG2A axis - Vietzen, Hannes; Simonitsch, Cara; Friedel, Benjamin; Berger, Sarah M.; Kühner, Laura M.; Furlano, Philippe L.; Florian, David M.; Görzer, Irene; Koblischke, Maximilian; Aberle, Judith H.; Puchhammer-Stöckl, Elisabeth (Frontiers in Immunology, 2024)
The ubiquitous Torque Teno Virus (TTV) establishes a chronically persistent infection in the human host. TTV has not been associated with any apparent disease, but, as part of the human virome, it may confer a regulatory imprint on the human immune system with as yet unclear consequences. However, so far, only few studies have characterized the TTV-specific immune responses or the overall immunological imprints by TTV. Here, we reveal that TTV infection leads to a highly exhausted TTVspecific CD8 + T cell response, hallmarked by decreased IFN-γ production and the expression of the inhibitory NKG2A-receptor. On a functional level, we identified a panel of highly polymorphic TTVencoded peptides that lead to an expansion of regulatory NKG2A + natural killer, NKG2A + CD4 + , and NKG2A + CD8 + T cells via the stabilization of the non-classical HLA-E molecule. Our results thus demonstrate that TTV leads to a distinct imprint on the human immune system that may further regulate overall human immune responses in infectious, autoimmune, and malignant diseases.